Determinants of Infant Mortality in Samdrup Jongkhar District, Bhutan - Pokhrel, Hari Prasad; Gyeltshen, Dawa; ., Tsheten; Sharma, Tulsi Ram; Tshewang, Pema; Dorji, Kezang; Yangzom, Dema (International Journal of Innovative Research in Medical Science, 2019)
Samdrup Jongkhar district has reported an increasing trend in infant mortality rates over the recent years. This study aimed to identify its determinants. A population based case-control study was conducted in May 2018. Case group comprised of 79 infants who died between 1st January 2015-30th April 2018 while 158 living children born during the same period and residing closest to the home where infant mortality occurred were recruited as controls. Premature new-borns and those with low birth weight were 5.9 times and 4.1 times more likely to die respectively. New-borns whose mother received better ante-natal and post-natal care were more likely to survive. Over 50% of the deaths occurred at home and around two-thirds of deaths occurred during the post-natal period. Implementing a multi-stakeholder collaborative approach including local leaders, village health workers and religious leaders would be useful in reassuring parents to seek early medical care during childhood illness.